Early Arabian Neolithic agropastoral communities from Asifir, Northwestern Saudi Arabia - Crassard, Rémy; Hilbert, Yamandú H.; Dinies, Michèle; Monchot, Hervé; Depreux, Bruno; Sahlah, Samer; Al-Badaiwi, Walid; Charloux, Guillaume (Archaeological and Anthropological Sciences, 2025)
Discovered during the survey of ancient Madyan, in the modern Al-Bad‘ oasis in north-western Saudi Arabia, the site of Asifir is distinguished by numerous surface concentrations of Neolithic artefacts. Low sediment mounds identified at the site indicated the possible preservation of in situ archaeological remains; one such mound was excavated in November 2019. Dated to the Early Arabian Neolithic period, Asifir is an open-air site located at the top of a conglomerate terrace along Wadi Ifal. The archaeology from the site is characterized by a high number of lithic artefacts, such as flakes, blades, and bladelets, as well as various lithic tools, including arrowheads, sickle blade insets, scrapers, borers, and grindstones. Personal ornaments such as small-sized worked shells and beads, are also present. The excavations have yielded a large hearth, with faunal (including mammals, birds and fish), malacological and botanical macro-remains. The archaeological evidence reveals the nature of the site as probably a dwelling place where domestic activities were performed. Presence of sickle blades with pronounced gloss represents a remarkable and unique find in Saudi Arabia, providing compelling evidence for cereal harvesting practices, possibly involving domesticated species such as Hordeum vulgare (barley). Asifir represents one of the rare sites in Saudi Arabia dating to this period, and one of the rare to indicate the use of agropastoral subsistence strategies in the region some 9000 years ago.
CRIS-Team Scopus Importer:2025-06-06
Keywords: Archaeobotany; Lithics; Neolithic; Saudi Arabia; Stratigraphy; Zooarchaeology